Gaya Pengurusan dan Kesannya Kepada Suasana Kerja di Badan-Badan Berkanun Negeri: Kajian Kes di Perbadanan Kemajuan Negeri Perlis - Ismail, Ahmad (1998)
This research has several purposes. Firstly, it intends to find out and identify the management styles that are being practised in the States’ Semi Government organizations. Four dimensions were chosen to represent management styles. They were Aloofness, Production Emphasis, Thrust and Consideration. Secondly, the research intends to find out the degree of working environment that has been achieved in the organisations as a result of the respective management styles. For this particular purpose the researcher choose four working dimensions, i.e. Disengagement, Hinderance, Esprit and Intimacy. The researcher disregards several factors that may have effect or influence on the variables. Thirdly, this research intends to identify whether there is a significant relationships between management styles and working environment. The research model had two basic components, i.e. management styles as an independent variable and the working environment as a dependent one. Lastly, the researcher gave suggestions and recommendations as to which management style would be the most suitable and most effective to be implemented in the States’ Semi Government organizations. The population of the study comprising of 44 respondents who are the employees of the Perbadanan Kemajuan Ekonomi Negeri Perlis (Perlis State Economic Development Corporation). They are of the Kumpulan Sokongan (Support Group), i.e. representing employees of B category and below. Only 42 (96%) of the respondents were successfully contacted by the researcher. Questionnaires consisting of 68 items were used to obtain feedback from the population. Data was analysed using Alpha Cronbach, percentage analysis, frequency, mean, mode, median, range, standard deviation and correlative test.